Penyuluhan dan Pelatihan Kegawatdaruratan Dental Serta Penanganannya Kepada Guru-guru SDI Assalam Joglo Jakarta Barat - Nova Adrian; Ferry Sandra; Ade Prijanti Dwisaptarini; Eka Seftiana Indahsari (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Dental emergencies are potentially life-threatening conditions and immediate treatment is needed to stop ongoing bleeding, reduce pain and also uncontrolled bleeding, cellulitis or bacterial tissue infection causing swelling in the mouth or mouth area and trauma to the bones in the facial area . Delay in treatment of trauma to the teeth can lead to treatment failure. Delay in emergency dental treatment after trauma will increase the risk of complications, non-vital teeth and an unpredictable prognosis.Dental emergencies often occur at the elementary school level and the most common cases are loose or avulsed teeth due to falls and impacts. Teachers in schools not only have a central role as educators, but teachers also act as first aid agents in dealing with health problems in schools. In addition, teachers also play a role and assist health workers in collecting data and also as the first emergency referral before being handled by health workers.SDI Assalaam has a staff of 46 teachers and 250 students. Having students who are actively moving has a risk of accidents such as falling and so on which can cause injury, especially the oral cavity, while knowledge of dental emergencies and their management according to the Principal of SDI Assalaam has never been received by the teachers who teach at SDI Assalaam , so that if there is a dental emergency the teachers don't know what action to take.To overcome the lack of knowledge about dental emergencies and their management. So the teachers of SDI Assalam are given counseling and training about dental emergencies and their handling so that the importance of dental emergencies is socialized so that teachers at SDI Assalaam can increase their knowledge about dental emergencies and their management.Based on the evaluation results of community service activities. There was a significant increase in the level of knowledge of SDI Assalaam teachers regarding dental emergencies and their treatment.